PENERAPAN SANKSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM (Perspektif UU No. 3 Tahun 1997) - Muhammad Fajrin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study aims to determine the forms of crimes committed by children and factors causing the rise of children in conflict with law and How the application of legal sanctions against children who have conflict with the law in Gowa district if reviewed under Act No. 3 of 1997 on Juvenile court. The research method used is deskrptip, based on the results of research that has been done in the results obtained that the factors that cause children conflict with the law that the occurrence of child crime in Kab. Gowa due to lack of harmony relationship between family and children consequently the influence of the environment outside the family more influence the way a child acts and feels like a child is outside the family, while based on table 1 page 42 Children who conflict with the law caused by the influence of less comfortable in the family environment , (Broken home) that is 73 people backed by the social environment influence 64 people, the influence of mass media as much as 40 people and the influence of personal and age is as many as 38 cases. But one thing that is very memprihatikan is the tendency that the frequency of all factors above the cause of the relative increase each year. So it demands the order of all parties to be pro active in anticipating it, especially from law enforcement officers and educators. Psychologically most children who commit criminal offenses are aged fourteen (14) years to 21 (twenty one) years, because at this time is a transition period from childhood to adulthood, where their soul development exists Tendency to: (1) want to be noticed; (2) Happy to fantasize; (3) Relying on His own; (4) Want to know more things like sexua, dal others. Implementation of Sanctions Against Children in Conflict With Law in gowa district has been basically done in accordance with the provisions of Law Number 3 Year 1997 starting from the stage of detention and investigation by the police, court and trial process. However, in the implementation of children in conflict with the law, at the stage of detention and investigation by the child police often get treatment that deviates from the provisions of Law No. 3 of 1997 in the form of torture and ill-treatment by police officers.